2016
DOI: 10.1007/978-3-319-45153-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Creating Effective Learning Analytics Dashboards: Lessons Learnt

Abstract: Learning Analytics (LA) dashboards help raise student and teacher awareness regarding learner activities. In blog-supported and inquiry-based learning courses, LA data is not limited to student activities, but also contains an abundance of digital learner artefacts, such as blog posts, hypotheses, and mind-maps. Exploring peer activities and artefacts can help students gain new insights and perspectives on learning efforts and outcomes, but requires effort. To help facilitate facilitate and promote this explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 40 publications
(44 reference statements)
2
29
0
3
Order By: Relevance
“…Dashboards have been developed for different stakeholder groups, including learners, teachers, researchers or administrative staff [35]. Charleer et al [5] suggest that LA dashboards could be used as powerful metacognitive tools for learners, triggering them to reason about the effort invested in the learning activities and learning outcomes. However, a large majority of dashboards are still aimed at teachers, or at both teachers and learners [35].…”
Section: Introductionsupporting
confidence: 43%
“…Dashboards have been developed for different stakeholder groups, including learners, teachers, researchers or administrative staff [35]. Charleer et al [5] suggest that LA dashboards could be used as powerful metacognitive tools for learners, triggering them to reason about the effort invested in the learning activities and learning outcomes. However, a large majority of dashboards are still aimed at teachers, or at both teachers and learners [35].…”
Section: Introductionsupporting
confidence: 43%
“…dashboards) exist, which visualize the different aspects of the learning process (Bodily et al 2018). Examples include learners' artifacts, time spent on tasks, social interaction, usage of resources, assignments and test results (Santos et al 2012;Lin et al 2016;Bull and Kay 2016;Charleer et al 2016;Verbert et al 2013). Experiences and guidelines for designing LA dashboards were discussed in Charleer et al (2016).…”
Section: Related Workmentioning
confidence: 99%
“…Examples include learners' artifacts, time spent on tasks, social interaction, usage of resources, assignments and test results (Santos et al 2012;Lin et al 2016;Bull and Kay 2016;Charleer et al 2016;Verbert et al 2013). Experiences and guidelines for designing LA dashboards were discussed in Charleer et al (2016). The authors suggested which data should be accessible to students (e.g., giving insight into the learning path to support reflection, peer comparison and self-regulated learning) and how to visualize it.…”
Section: Related Workmentioning
confidence: 99%
“…This point was further articulated by one participant, who suggested 'perceived objectivity…because you have to do something with the data to get something out of it.' In addition, the power to visualise data and provide immediate feedback to both teachers and students was frequently noted by several participants, as highlighted by recent research (Charleer, Klerkx, Duval, De Laet, & Verbert, 2016;Nguyen et al, 2017). Furthermore, two additional participants noted that learning analytics can measure 'a lot of things at the same time,' while most educational researchers primarily have to be selective in terms of the instruments and constructs that can be collected or measured.…”
Section: Rq 1 Main Strengths and Limitations Of Learning Analyticsmentioning
confidence: 99%